RATIONAL RESEARCH METHODS FOR OPTIMIZING SOLAR THERMAL-CHEMICAL TREATMENT MODES FOR HIGHLY FILLED ASH-CEMENT COMPOSITIONS OF FINE-GRAINED STRUCTURE - Prof. A. Kh. Alinazarov; J. Kh. Salimjonov (Journals Park Publishing, 2024)
The transition to the production of naturally hardened stones or those hardened under conditions of heat and moisture treatment using solar energy will increase purchasing power and consumer demand for wall materials, modernize or create production facilities with minimal investment and increase the volume of production of individual wall materials, reduce the consumption of conventional fuel for their production by about 350 thousand tons, and electricity by 400 million kW/hour. In this aspect, the development of energy- and resource-saving technology for obtaining highly filled gold-cement materials and obtaining various products on their basis with their subsequent heat and moisture treatment using solar energy is of great scientific and practical interest.
Keywords: Thermal power plant, fly ash, ash-cement, granulation, solar energy, vacuum pump mixer, modified plasticizing additive.